Kendali Penyimpan Energi Listrik untuk Aplikasi Mikrogrid - Hilman Zarory; F. Danang Wijaya; Bambang Sutopo (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2014)
The design of the inverter control system aims to regulate active power and reactive power flows from the batteries through the three-phase inverter. Reference power generated manually to compensate the active and reactive power required by microgrid. Modelling done by the transformation clarke-park to design close loop system with PI (Proportional Integral) control so that the current flows in the inverter is maintained at the reference value. PLL (Phase Locked Loop) is used to synchronize inverter and grid. The simulation result shows that the system can work very well and the voltage or frequency of microgrid maintained under normal conditions.